An Assessment of Extension Officers’ Self-Perceived Programming Competencies in Selected Caribbean Countries - Amy Harder; Wayne Ganpat; Austen Moore; Robert Strong; James R Lindner (Journal of International Agricultural and Extension Education, 2013)
Developing the human capacity of extension systems is a necessary part of improving services intended to meet the needs of small farmers. The purpose of this study was to determine the competencies for which professional development is needed in the area of programming for extension officers in selected Caribbean countries. A survey was conducted with all extension officers attending in-service trainings in Belize, Grenada, and Saint Lucia, using the Borich method to identify priority training needs. The greatest needs were most frequently observed in the areas of program planning and evaluation, although considerable variation existed across the group. The resulting challenge is to develop professional development resources that can be individualized by country while remaining cost-effective and accessible
Keywords: Extension; Programs; Professional Development; Needs Assessment